An Implementation of Reflective Pedagogy in Hybrid Music Learning of Gamelan Soepra - Pamungkas, Benidiktus Candra; Utomo, Udi; Sumaryanto Florentinus, Totok (Universitas Negeri Semarang, 2020)
Gamelan Soepra is a gamelan instrument that has been changed in tonality to diatonic and has a higher wadhah. With its diatonic tonality, Gamelan Soepra is able to be combined with today's modern instruments and it is able to play many song. The uniqueness of the Gamelan Soepra was used by Pater van Deinse as a music education at SMA Kolese Loyola. Gamelan Soepra is a tool for educating thar is combined with reflective pedagogy as an educational method. Reflective pedagogy has several elements, namely: context, experience, reflection, action, and evaluation. This study aims to understand the implementation of the reflective pedagogy elements in the learning process of Gamelan Soepra. The methods used by the author in collecting data were observation, interview, and document study. Gamelan Soepra Learning through reflective pedagogy not only develops students' abilities in playing music (Competence), but students also are trained to hone and develop their conscience (Compassion), conscience and their commitment and responsibility to what they have chosen (Commitment). This s is study expected to be a reference for developing learning methods, especially music learning